Kontribusi Sertifikasi Halal terhadap Peningkatan Kualitas Produk dan Layanan pada Rumah Makan - Ana Mardinatul Ilmi; Aslikhah; Sukamto (Kartika: Jurnal Studi Keislaman, 2026)
Halal certification serves as a essential mechanism in guaranteeing the halal status, safety, and standard of food products available to the public. As competition intensifies within the culinary sector, entrepreneurs are expected not only to offer halal food but also to ensure product and service quality that aligns with consumer expectations. This research was prompted by the heightened awareness among Muslim consumers regarding the significance of halal guarantee as a marker of product reliability. The objective of this study is to examine how halal certification implementation enhances product and service quality at three restaurants M2M, Geprek Sa'i, and Ayam Goreng Nelongso situated in Pandaan District, Pasuruan Regency. This investigation utilized a qualitative methodology with a multiple-case study framework. Data gathering was performed through direct observation, comprehensive interviews, and archival records engaging owners, staff, and customers. The analytical process applied the Miles, Huberman, and Saldana interactive model, encompassing data condensation, data presentation, and deriving insights. The results demonstrate that halal certification implementation plays a role in elevating product quality via utilizing halal-verified ingredients, sanitary production methods, and ongoing quality monitoring. Moreover, halal certification elevates service quality by fostering courteous, proficient, and dependable customer interactions. This research suggests that halal certification operates not merely as regulatory adherence but also as a strategic instrument to enhance market competitiveness and consumer confidence within the culinary sector